Catheter ablation versus pharmacological treatment for patients with Wolff-Parkinson-White syndrome - Oliveira, Gabriela R.; Petiti, Daniel; Garbelini, Benito J.; de Oliveira Carvalho, Paulo Eduardo; Cataneo, Antonio José Maria [UNESP] (Wiley, 2013)
This is the protocol for a review and there is no abstract. The objectives are as follows: To evaluate the effectiveness and safety of ablation compared with drug therapy for patients with WPW syndrome.